Study of the Struck-By Hazard in the Application of Ultrasound Sensor in Construction Safety - P. Vishal; M. Kranti Kumar (Current Overview on Science and Technology Research Vol. 5, 2022)
Compared to modern construction sites, traditional building sites were easier, and safety management was created to solve these simpler construction difficulties. Because of its ability to perform automatic tasks and realtime monitoring, sensors can currently be used in construction safety management to provide the necessary level of safety for site complexity. The study’s goal is to analyse the suitability of various sensor technologies for use in struckby hazard prevention systems and to assess the effectiveness of sensors in shielding construction sites from such risks. The construction sector is currently under pressure to finish projects as quickly as possible while also achieving the goal of safety, as managing construction sites is becoming more difficult. An early warning system using ultrasound sensors is suggested to manage complex facilities and guard against potential threats. Since new construction techniques are being used at such complicated sites and in response to quick, continual changes in construction sites, managing current construction sites with old safety management approaches makes them challenging to monitor. The proposed early warning system will aid site managers in running their jobs more efficiently. On strike-by danger prevention in construction, numerous researchers have conducted numerous studies. However, there isn’t enough attention paid to it, especially when using ultrasound sensors to guard against potential threats. Therefore, it has been determined how well ultrasound sensors can be used in this field of building.